2020
DOI: 10.1002/pmic.201900405
|View full text |Cite
|
Sign up to set email alerts
|

In Depth Quantitative Proteomic and Transcriptomic Characterization of Human Adipocyte Differentiation using the SGBS Cell Line

Abstract: Most information on molecular processes accompanying and driving adipocyte differentiation are derived from rodent models. Here, a comprehensive analysis of combined transcriptomic and proteomic alterations during adipocyte differentiation in Simpson–Golabi–Behmel Syndrome (SGBS) cells is provided. The SGBS cells are a well‐established and the most widely applied cell model to study human adipocyte differentiation and cell biology. However, the molecular alterations during human adipocyte differentiation in SG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
(29 reference statements)
2
9
0
Order By: Relevance
“…This study helps our understanding of the complicated metabolic events that occur in relation to the changes in metabolic enzymes involved in adipocyte differentiation. Previous proteomics studies on adipogenesis have reported that PPARγ signaling, TCA cycle, lipid metabolism, fatty acid β-oxidation metabolism, electron transport chain, and redox system were up-regulated in adipocyte differentiation. Our proteomic results are confirmatory of these previous findings. In addition, we identified additional proteins such as those involved in nicotinamide metabolism, those that induced changes in cristae and mitochondrial protein import, and in the transport of Ca 2+ into mitochondria and ER.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study helps our understanding of the complicated metabolic events that occur in relation to the changes in metabolic enzymes involved in adipocyte differentiation. Previous proteomics studies on adipogenesis have reported that PPARγ signaling, TCA cycle, lipid metabolism, fatty acid β-oxidation metabolism, electron transport chain, and redox system were up-regulated in adipocyte differentiation. Our proteomic results are confirmatory of these previous findings. In addition, we identified additional proteins such as those involved in nicotinamide metabolism, those that induced changes in cristae and mitochondrial protein import, and in the transport of Ca 2+ into mitochondria and ER.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to our study, a recent SILAC based-quantitative proteomics investigation of human adipocytes has reported that adipogenic markers and many other proteins from the lipid metabolic pathways are up-regulated during differentiation of the human Simpson−Golabi−Behmel syndrome (SGBS) adipocytes. 78 Journal of Proteome Research Proteins annotated in neXtProt knowledgebase, inclusive of PE, splice isoform, and uPE, are subject for a future study in order to verify their expression and potential functions in adipocytes.…”
Section: ■ Discussionmentioning
confidence: 99%
“…4e). This finding is consistent with previous data showing that TG and DG are the main components of SGBS lipid contents during differentiation 18 . Notably, 17 out of the 19 top differentially expressed TG molecules contain C18:1 (Fig.…”
Section: Mir-1304-3p Activates Cancer-associated Adipocytessupporting
confidence: 94%
“…suggesting that this cell line might be useful for assessments of adipocyte browning. Proteomic and transcriptomic analyses of SGBS cells have been used to evaluate the molecular underpinnings of SGBS differentiation, with >1100 proteins and >300 genes differentially expressed in differentiated cells relative to undifferentiated [58]. However, some research comparing this model to existing models has suggested notable differences.…”
Section: Preadipocyte Modelsmentioning
confidence: 99%